ڕۆڵی زانکۆ لە گەشەپێدانی مەعریفەی جێندەریی - محمد, پ.ی.د.کەژاڵ حسین; عبدللە, سورێن ابوبکر (Sulaimani Journal for Humanities, 2023)
It has been found that the knowledge society of any society is the result of social reality and the way of developing such knowledge, since these two variables are inextricably linked and establish the type and nature of this knowledge in the social structure Because of the need and importance for analyzing and interpreting some of the social phenomena and problems related to the social life of individuals, when we focus on the universities of the Kurdistan Region as one of the institutions for the development of gender knowledge in society It plays a role in building a knowledge society through academic lectures in some departments, scientific research, activities, conferences and the existing of gender and equality centers. However, these efforts are not adequate to build a knowledge society and there are many obstacles that affect how this kind of knowledge is developed in universities, for example The main reasons form research sample, are the lack of experts, cultural barriers and university management systems. Therefore, the necessary development in the field of gender knowledge has not been achieved and the knowledge is framed in a very simple and superficial stage.
Keywords: Gender; Gender Knowledge; Development